2001
DOI: 10.1076/apab.109.4.331.4248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxidative Stress in Patients with Cancer

Abstract: The oxidative stress is considered to be involved in the pathophysiology of cancers. In the current study we explored the oxidative stress in patients with different cancers and corresponding benign diseases by evaluation of the level of lipid peroxidation products (MDA level) in the plasma and the activity of erythrocyte antioxidant defense enzymes superoxide dismutase (SOD) and catalase (CAT). Significantly higher plasma levels of lipid peroxidation products were detected in patients with early and advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 27 publications
2
19
0
1
Order By: Relevance
“…Namely, in all examined groups higher levels of LOOH were recorded than in controls, though the elevation was not significant only in patients with polypus endometrii. The increase in LOOH may also be due to the impaired antioxidant system as observed in the previous studies (26,22). We also observed that circulating levels of lipid hydroperoxides are generally higher in subjects with either form of hyperplasia or adenocarcinoma than those found in polypus or myoma patients.…”
Section: Discussionsupporting
confidence: 54%
“…Namely, in all examined groups higher levels of LOOH were recorded than in controls, though the elevation was not significant only in patients with polypus endometrii. The increase in LOOH may also be due to the impaired antioxidant system as observed in the previous studies (26,22). We also observed that circulating levels of lipid hydroperoxides are generally higher in subjects with either form of hyperplasia or adenocarcinoma than those found in polypus or myoma patients.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have reported both increased and decreased erythrocytes catalase activity in oral cancer patients. [38][39] In the present study, erythrocyte catalase activity was significantly elevated in WHT and patients with OPC than NHT. However, erythrocyte catalase activity was decreased in oral cancer patients than OPC.…”
Section: Discussionmentioning
confidence: 76%
“…Hristozov et al, found significantly higher levels of lipid peroxidation products (malonaldehyde) in early and advanced cancers in comparison to controls. [38] Das, suggested that tumor cells have relatively low amounts of SOD, which quenches superoxide anion and as a result of a higher level of aerobic metabolism, higher concentration of hydroxyl ion compared with normal cells. He also suggested that ionizing ration radiation and chemotherapeutic agents like anthracyclines and bleomycin exert their anticancer effect by the producing free radicals.…”
Section: Mode Of Actionmentioning
confidence: 98%